Gravitational wave sources from inspiralling globular clusters in the Galactic Centre and similar environments - Arca Sedda, Manuel; Gualandris, Alessia (Monthly notices of the Royal Astronomical Society, 2018)
Abstract. We model the inspiral of globular clusters (GCs) towards a galactic nucleus harbouring a supermassive black hole (SMBH), a leading scenario for the f
Gesehen am 05.02.2019